2011
DOI: 10.1177/1044207311424909
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Students Who Take an Alternate Assessment Based on Modified Achievement Standards

Abstract: Alternate assessments based on modified achievement standards (AA-MAS) are designed to measure the academic achievement of students with disabilities who are not expected to reach grade-level standards but who do not qualify for alternate assessments based on alternate achievement standards (AA-AAS). This article describes the 2010 participants of one state's AA-MAS. AA-MAS test-takers included a higher proportion of males than were recorded for the general test, and they were more likely than other students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…They also found special education students identified as "low performing" in Year 1 of the data set were more likely to become persistently low performing on state reading and mathematics assessments than their lowperforming non-special education peers. These findings were further confirmed in a study by Shaftel and Rutt (2011) that examined data from another state. Shaftel and Rutt found that students who participated in the AA-MAS were "more likely to be of minority ethnicity, to be English language learners, and to experience poverty" (p. 1) than students who participated in the regular assessment.…”
Section: The Characteristics Of the Studentssupporting
confidence: 80%
See 2 more Smart Citations
“…They also found special education students identified as "low performing" in Year 1 of the data set were more likely to become persistently low performing on state reading and mathematics assessments than their lowperforming non-special education peers. These findings were further confirmed in a study by Shaftel and Rutt (2011) that examined data from another state. Shaftel and Rutt found that students who participated in the AA-MAS were "more likely to be of minority ethnicity, to be English language learners, and to experience poverty" (p. 1) than students who participated in the regular assessment.…”
Section: The Characteristics Of the Studentssupporting
confidence: 80%
“…Many low-performing students, both with and without disabilities, are from subgroups that historically have been denied access to high-quality instruction (ethnic/racial minorities, low socioeconomic status; Perie, Fincher, Payne, & Swaffield, 2012;Shaftel & Rutt, 2011). Quenemoen (2010) asked, "What evidence exists to suggest that students with disabilities who are low-performing differ from minority students or poor students who are low-performing?"…”
Section: Discussion and Policy Implicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, the majority of students taking the MAS were male, which was below their overall proportion of 60% in special education statewide. Interestingly, the characteristics of students in Connecticut that participated in the MAS were similar to students in one Midwestern state documented by Shaftel and Rutt (2012) in their study of modified assessment demographics.…”
Section: "Addition Through Subtraction": Removing Children With Disab...mentioning
confidence: 59%